2019
DOI: 10.4314/tjpr.v18i2.22
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the interaction between ciprofloxacin hydrochloride and diclofenac sodium

Abstract: Purpose: To study the interaction between ciprofloxacin hydrochloride (Cipro) and diclofenac sodium (DS) in the presence and absence of metal ions. Methods: Complexes were prepared in the aqueous phase at different molar ratios (r) of Cipro:DS (ranged from 0.2-2.0). The complexes were characterized by Fourier transform-infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR), and high pressure liquid chromatography (HPLC). Their properties, i.e., solubility, dissolution and partition coefficient (log P),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Solubility and apparent partition coefficient studies were performed in triplicate as previously described (8). Briefly, the excess solid material of CP or any of the prepared salts was added to 4 mL of phosphate buffer (pH 6.8), left on a shaker water bath for 24 h and then 1 mL was centrifuged.…”
Section: Solubility and Partition Coefficient Of The Prepared Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solubility and apparent partition coefficient studies were performed in triplicate as previously described (8). Briefly, the excess solid material of CP or any of the prepared salts was added to 4 mL of phosphate buffer (pH 6.8), left on a shaker water bath for 24 h and then 1 mL was centrifuged.…”
Section: Solubility and Partition Coefficient Of The Prepared Saltsmentioning
confidence: 99%
“…Further investigations IMAD I. HAMDAN 1 DINA EL-SABAWI 2 RULA DARWISH 2 LINA A. DAHABIYEH 1, * from our laboratory, revealed that DS forms ion-pair salts with CP. The resulting salts were shown to have modified physicochemical properties, partition coefficient and, to some extent, antimicrobial activity (8). Ternary associates, involving one molecule of CP and two molecules of DS, have also been shown to form, and, interestingly, possess solubilities different than that of CP or its 1:1 salt.…”
mentioning
confidence: 99%
“…The physiological response, alteration of siphon e ciency, has been frequently regarded as an index to evaluate the function of freshwater bivalves in ecology and bioremediation (Hills et al 2020). A previous research has demonstrated that 2.5 µg/L cipro oxacin (CIP), another commonly human pharmaceutical, could signi cantly inhibit the siphon e ciency of Corbicula uminea (El-Sabawi et al 2019;Guo et al 2021). However, whether DCF has the same impact on siphon behavior of bivalves is unclear.…”
Section: Introductionmentioning
confidence: 99%